2018
DOI: 10.1016/j.ijfoodmicro.2017.12.030
|View full text |Cite
|
Sign up to set email alerts
|

Anisakis spp. larvae in different kinds of ready to eat products made of anchovies ( Engraulis encrasicolus ) sold in Italian supermarkets

Abstract: In this study the occurrence of visible anisakid larvae in semi-preserved anchovy products sold on the Italian market was investigated. Totally, 107 ready to eat products (33 salted-ripened, 49 in oil and 25 marinated) were sampled. Each sample was digested, then the digested material was observed under natural and UV light. Parasites were counted, collected and microscopically identified to genus level. A representative subset was molecularly identified using the cox2 gene. At least one visible Anisakis sp. l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 38 publications
3
21
0
Order By: Relevance
“…(1.1%) and unspecified tapeworms (0.5%). Finally, one notification (0.5%) regarded swordfish fillets because of the presence of Pennella, which, although not dangerous for human health, can make products unfit for consumption (Guardone et al, 2018).…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…(1.1%) and unspecified tapeworms (0.5%). Finally, one notification (0.5%) regarded swordfish fillets because of the presence of Pennella, which, although not dangerous for human health, can make products unfit for consumption (Guardone et al, 2018).…”
Section: Figmentioning
confidence: 99%
“…are available in the literature (Wharton, Hassall, & Aalders, 1999). Although in this case, the squids were frozen and thus larvae were inactivated, dead parasites are an increasing reason to consider products unfit for consumption (Bilska-Zając et al, 2016;Guardone et al, 2018).…”
Section: Category Of Hazard In Cephalopodsmentioning
confidence: 99%
“…The most commonly affected commercial species are hake, whiting, cod, and mackerel, but the parasite has also been identified in a large variety of fish such as sole, john dory, sea bream, horse mackerel, herring, blue whiting, sardine, anchovy, haddock, monkfish, salmon, conger, and turbot, and in cephalopods, such as squid, octopus and cuttlefish [4][5][6][7]. We should also point out that studies confirm that the preva-lence in fish varies according to the fishing area and the size of the host, with larger fish having more infestations [7,8].…”
Section: Geographical Distributionmentioning
confidence: 99%
“…However, over the last few years there has been an increase in the number of cases reported in other countries including Italy [8,12] and Spain [6,13].…”
Section: Pathogenesismentioning
confidence: 99%
“…Most of the larvae are found on the visceral surface of the gastrointestinal tract and to a much lesser extent embedded in fillets [17,18]; however, Šimat et al showed that A. pegreffii larvae persist in anchovy fillets of live fish and that post-mortem migration during storage at both 0 and 4 • C is delayed by 3-5 days but still presumptive [22]. A recent study found significant numbers of dead Anisakis larvae in ready-to-eat products made of anchovies on the Italian market, which in addition to posing health risks for sensitized consumers, also represents extremely unpleasant experiences and can inflict economic losses [24].…”
Section: Introductionmentioning
confidence: 99%